Territorial Information System and the Enhancement of Territorial Governance Mechanisms in the Countryside of Taourirt Province (Eastern Region – Morocco) - LAKHDARI, Mohammed; ELBAZOUI, JAOUAD; AZIACH, Mohamed (Journal of Humanities & Social Sciences, 2024)
The digitization of databases and the integration of artificial intelligence mechanisms paly a crucial role in enchancing territorial governance within contemporary territorial management frameworks. These endeavors are essential for aligning with developmental strategies, assessing interventions, and analyzing their outcomes. The territorial information system acts as a central instrument for harmonizing various stakeholders (such as institutions, elected representatives, property holders, universities, political entities, and associations) with computer systems and databases. Its primary ai mis to generate knowledge that forms a robust basis for stakeholder activities. The research underscores the significance of databases and websites in fortifying territorial governance in the Countryside of Taourirt Province. Through the monitoring and evaluation of interventions, as well as the systematic and timely updating of data, these tools amplify the efficacy of developmental projects in the area. Additionally, the availability of well-structured and centralized data, accessible to institutional stakeholders, elected representatives, and property holders, facilitates convenient access regardless of the stakeholder or location. This sustained usability, coupled with its flexibility and potential for enchancement, further accentuates its importance and ability to strengthen torritorial governance.